2014
DOI: 10.1111/jvp.12187
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐articular administration of lidocaine in anaesthetized dogs: pharmacokinetic profile and safety on cardiovascular and nervous systems

Abstract: The intra-articular administration of lidocaine is a frequent practice in human orthopaedic surgical procedures, but an eventual absorption of the drug into the bloodstream can lead to toxicity, mainly concerning the central nervous system and the cardiovascular systems. The purpose of this study was to determine the pharmacokinetic profile and the safety, in terms of cardiovascular and CNS toxicity, of lidocaine after intra-articular administration to anesthetized dogs undergoing arthroscopy. Lidocaine 2% was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…This value is approximately half of that observed in a similar study (2.18 ± 0.91 µg/mL; Di Salvo et al, 2014), where 2% lidocaine was administered by the IA route without the addition of adrenaline. Narchi et al (1992) also observed a reduction in the C max to approximately half after the intraperitoneal administration of a solution of 0.5% lidocaine plus adrenaline (1:800,000 and 1:320,000), compared to the values obtained after the administration of lidocaine alone.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…This value is approximately half of that observed in a similar study (2.18 ± 0.91 µg/mL; Di Salvo et al, 2014), where 2% lidocaine was administered by the IA route without the addition of adrenaline. Narchi et al (1992) also observed a reduction in the C max to approximately half after the intraperitoneal administration of a solution of 0.5% lidocaine plus adrenaline (1:800,000 and 1:320,000), compared to the values obtained after the administration of lidocaine alone.…”
Section: Discussionmentioning
confidence: 45%
“…The results showed that the maximum concentration of lidocaine reached was 2.188 µg/mL, which was lower than that indicated by Lemo et al (2007) as responsible for the appearance of neurotoxic effects. In the study conducted by Di Salvo et al (2014) with lidocaine alone concentrations > 2.7 ± 1.1 µg/mL were reached. As that study was conducted using the same protocol as the present study (the only difference was the presence or the absence of adrenaline) it is possible to postulate that the addition of adrenaline, which slows the absorption of lidocaine, does not allow blood concentrations high enough to cause neurological adverse effects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…4 Anti-inflammatory and analgesics drugs are a classic, acute phase therapeutic resource, with a very old history of fast and long acting corticosteroids with facultative addition of lidocaine or other derivatives. Lidocaine, a local anesthetic was originally used to prevent the needle sticking pain of skin, subdermal layers, and synovial membrane (5). Finally, once spread into the joint cavity, it allows painless immediate motility and earlier functional recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, once spread into the joint cavity, it allows painless immediate motility and earlier functional recovery. 5 Furthermore, local anesthetics induce chondrocyte and synovial cell apoptosis. Ropivacaine and bupivacaine had limited toxicity in human mesenchymal stem cells, but lidocaine has shown to reduce mesenchymal stem cell viability.…”
Section: Resultsmentioning
confidence: 99%